Parathyroid Hormone Status in Patients with End Stage Renal Disease on Maintenance Haemodialysis (BIRDEM Medical Journal, 2014)
Objective: To evaluate parathyroid hormone (PTH) status among end stage renal disease (ESRD) patients on maintenance haemodialysis (MHD). Methodology: This descriptive cross-sectional study was done in the Department of Nephrology, BIRDEM General Hospital, Dhaka, from April to September 2011. Results: A total of 50 patients were included in this study with a 3:2 male predominance. Mean age was 54.6 (range 34-76) years. Mean duration of ESRD was 3.73 years. All the patients were diabetic and other common co-morbidities were hypertension (76%), dyslipidaemia (56%), ischaemic heart disease (48%) and stroke (12%). They were receiving calcium (72%), vitamin D (40%), both calcium and vitamin D (38%) supplementation and 20% were not on any medication for treatment of chronic kidney disease mineral bone disorder (CKD-MBD). Mean pre-dialysis values of urea and creatinine were 30.28 mg/dl and 8.67 mg/dl respectively. Mean (± SD) serum level of calcium, phosphate and PTH were 8.32 (±1.26) mg/dl, 4.42 (±1.54) mg/dl and 125.45±117.71 pg/ml respectively. In 76% of the study subjects, PTH level was above normal. Significant difference (P=